Risk Management Evaluation Based on ISO/IEC 27005 Framework: A Case Study of ABC Company IT Workshop Room - Muhammad Ferdi Kurniawan; Triana Dewi Salma (International Journal Software Engineering and Computer Science (IJSECS), 2025)
ABC Company operates as a technology firm based in France, maintaining its research and development operations in Jakarta. The company produces digital security technologies—biometrics, facial recognition systems, and digital identity solutions—alongside telecommunications and payment products including SIM cards, banking cards, and smart cards. Given how much the company relies on technology and secure information handling, it needs strong systems and infrastructure, especially when dealing with sensitive data. Yet no one has conducted a risk management assessment of the IT workshop room. Several problems have emerged with the physical security of this important area, such as people misusing access privileges and assets going missing. This research evaluates how the company manages information security risks by first identifying what's causing these problems through a fishbone diagram that looks at people, technology, and processes. We then assessed risks using the ISO/IEC 27005:2018 standard across 12 assets, examining threats, current controls, weak points, and what treatments are needed. Our analysis shows three assets (A5, A6, A7) carry high risk, three others (A4, A9, A12) have medium risk, and six assets (A1, A2, A3, A8, A10, A11) present low risk. Using these results, we developed specific recommendations for handling risks associated with each asset to improve information security throughout the company.